2015
DOI: 10.15252/embj.201591245
|View full text |Cite
|
Sign up to set email alerts
|

RuvbL1 and RuvbL2 enhance aggresome formation and disaggregate amyloid fibrils

Abstract: The aggresome is an organelle that recruits aggregated proteins for storage and degradation. We performed an siRNA screen for proteins involved in aggresome formation and identified novel mammalian AAA+ protein disaggregases RuvbL1 and RuvbL2. Depletion of RuvbL1 or RuvbL2 suppressed aggresome formation and caused buildup of multiple cytoplasmic aggregates. Similarly, downregulation of RuvbL orthologs in yeast suppressed the formation of an aggresome-like body and enhanced the aggregate toxicity. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 70 publications
(122 reference statements)
0
41
0
Order By: Relevance
“…In this model, the Rvbs would primarily play a role in regulating subunit stoichiometry. In the second alternative model, the ATPase stimulation caused by Ino80INS may reflect the Rvbs’ potential role for remodeling protein complexes, as Rvb1 and Rvb2 have been hypothesized to be involved in disaggregation of amyloid fibrils (Zaarur et al, 2015) and chromosome decondensation (Magalska et al, 2014). Importantly, our observation that protein, not nucleic acid, is a robust activator of Rvb1/Rvb2 helps exclude models involving a helicase-like role of the Rvbs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, the Rvbs would primarily play a role in regulating subunit stoichiometry. In the second alternative model, the ATPase stimulation caused by Ino80INS may reflect the Rvbs’ potential role for remodeling protein complexes, as Rvb1 and Rvb2 have been hypothesized to be involved in disaggregation of amyloid fibrils (Zaarur et al, 2015) and chromosome decondensation (Magalska et al, 2014). Importantly, our observation that protein, not nucleic acid, is a robust activator of Rvb1/Rvb2 helps exclude models involving a helicase-like role of the Rvbs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PrP repeats to functionally substitute for those of Sup35 in [ PSI + ] maintenance suggests that they could play a similar role in mammals. Recent studies have identified potential candidates for this function, including the AAA+ ATPase RuvbL [102] or the combination of Hsp70, DNAJB1, and Hsp110 [103], although their contributions to mammalian prion propagation have not yet been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…First and foremost, cross-linking can take a snap-shot of real-time dynamic interaction networks on the scale of the entire interactome in vitro and in vivo [8][9][10]. Also, cross-linking can not only identify the direct interacting partners but also determine the interaction sites at the same time.…”
Section: Strengths and Challenges Of Chemical Cross-linking Mass Specmentioning
confidence: 99%
“…GPMAW is suitable for small-scale analysis. xQuest can be used for large proteome-wide cross-linking studies [8,9].…”
Section: Cross-linking Identification Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation